2013
DOI: 10.1371/journal.pone.0065244
|View full text |Cite
|
Sign up to set email alerts
|

Random Effects Models and Multistage Estimation Procedures for Statistical Population Reconstruction of Small Game Populations

Abstract: Recently, statistical population models using age-at-harvest data have seen increasing use for monitoring of harvested wildlife populations. Even more recently, detailed evaluation of model performance for long-lived, large game animals indicated that the use of random effects to incorporate unmeasured environmental variation, as well as second-stage Horvitz-Thompson-type estimators of abundance, provided more reliable estimates of total abundance than previous models. We adapt this new modeling framework to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Program PopRecon 2.0 produces estimates of age‐ and year‐specific abundance values and associated standard errors using the Horowitz–Thompson approach of Gast et al (,). Estimates of abundance for the youngest age class may also be considered an estimate of net annual recruitment for the population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Program PopRecon 2.0 produces estimates of age‐ and year‐specific abundance values and associated standard errors using the Horowitz–Thompson approach of Gast et al (,). Estimates of abundance for the youngest age class may also be considered an estimate of net annual recruitment for the population.…”
Section: Resultsmentioning
confidence: 99%
“…From the model fitting, recruitment numbers and population abundance are estimated either explicitly as in the case of Gove et al () or through a 2‐phase estimation process as in Gast et al (). In Program PopRecon, we used the Horvitz–Thompson approach advocated by Gast et al (,) where annual abundance is estimated by escalating the harvest counts by the estimated harvest and reporting rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We modeled partial observability by substituting an estimate of male abundance ( N̂ ) for the true abundance ( N ) in harvest models, mimicking a situation where male abundance estimates are used to update target harvests over time in a state‐dependent manner. We simulated abundance estimates as normal random variables, Nˆm,s,t~Normal(Nm,s,t,σtrueNˆm,s,t), with the mean centered on the true abundance of males ( m ) at the start of spring hunting ( s ) in year t (Nm,s,t) and a constant coefficient of variation (σtrueNˆm,s,tgoodbreakinfix=CVtrueNˆm,sgoodbreakinfix×Nm,s,titalic; Supplement 1, available online in Supporting Information) that was estimated empirically from abundance estimates generated by Gast et al (). To understand the effects of partial observability on performance of harvest policies, we also replicated all simulations without observation error, assuming σtrueNˆm,s,t= 0 and therefore Nˆm,s,tgoodbreakinfix=Nm,s,t.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated standard errors from a numerical estimate of the inverse Hessian (Skalski et al 2012b, Gast et al 2013a,b) using the numDeriv package (Gilbert and Varadhan ). Because these reconstruction models consistently underestimate uncertainty (Gast ), we inflated all standard errors and confidence intervals by the goodness‐of‐fit scale parameter suggested by Skalski et al (, ): χdf2df, where the χ2 statistic is based on the observed age‐at‐harvest data (hij) and their expected values under the fitted likelihood model.…”
Section: Methodsmentioning
confidence: 99%